Assessing gene action for hypoxia tolerance in cotton (Gossypium hirsutum L.) - Hussain, Altaf (2019)
Introduction. The inheritance studies on hypoxia tolerance in cotton are very scanty. Objective. The objective of this work was to study the inheritance pattern of seed cotton yield, ginning out-turn, and fiber length under normal and hypoxia conditions. Materials and Methods. An 8•8 diallel mating system was employed in F1 generation of cotton. The experiment was conducted during the years 2011-2012 at Cotton Research Institute, Multan, Pakistan. Results. Analysis of variance revealed significant variation (P<0.01) for all the traits under both non-stress and flooding stress conditions. The value of regression coefficient b deviated significantly from zero but not from unity for all the traits which enabled further analysis of the data. The additive component (D) was significant for all the traits and this has more values than the values of dominance components H1 and H2, which clearly indicates the preponderance of additive genetic effects. Under normal and hypoxia conditions the estimates of narrow sense heritability were higher. Conclusion. Predominance of additive genetic effects, high heritability along with partial dominance under both conditions suggested that selection for these traits under hypoxic environment at early generation will be useful.